Incidence of Advanced Colorectal Neoplasia in Individuals With Untreated Diminutive Colorectal Adenomas Diagnosed by Magnifying Image-Enhanced Endoscopy. (June 2019) - Sekiguchi, Masau; Otake, Yosuke; Kakugawa, Yasuo; Matsumoto, Minori; Tomizawa, Yutaka; Saito, Yutaka; Matsuda, Takahisa
Abstract : OBJECTIVES: Because of the increasing number of detected diminutive colorectal adenomas, the "diagnose-and-do-not-resect" approach has recently attracted attention as an alternative to resection. We evaluated the cumulative incidence of advanced colorectal neoplasia (ACN) in individuals with untreated diminutive adenomas and compared this incidence in individuals without adenomas. METHODS: Data from 1, 378 individuals who underwent first screening colonoscopy (CS) and at least one follow-up CS without polypectomy were analyzed. Patients with no adenomas or with only nonadvanced diminutive adenomas (<5 mm) diagnosed by magnifying image-enhanced endoscopy were scheduled to undergo a follow-up CS within 5 years after the initial CS without treatment. The participants were divided into 2 groups: those with untreated diminutive adenomas (group A) and those with no adenomas (group B). The cumulative incidence of ACN and the hazard ratio were assessed using Gray's test and the Fine and Gray model. RESULTS: During the median follow-up period of 60.9 months, 21 ACNs were detected. The 5-year cumulative incidences of ACN in group A (n = 361) and group B (n = 1, 017) were 1.4% (95% confidence interval [CI]: 0.5–3.4) and 0.8% (95% CI: 0.3–1.7), respectively, without a statistically significant difference ( P = 0.23). No ACNs developed from unresected adenomas. The smoking status was significantly associated with the incidence of ACN, and the hazard ratio for ACN in group A vs group B adjusted for smoking status was 1.43 (95% CI: 0.52–3.90; P = 0.48). DISCUSSION: The low 5-year cumulative incidence of ACN suggests the potential to adopt the "diagnose-and-do-not-resect" strategy as an alternative option for diminutive adenomas not requiring excessive surveillance.